مفهوم الدعوة وفريضتها - The concept of Islamic da’wah and it’s obligation - Hashim, Jamil; Ahmad, Masitoh (Kolej Islam Darul Ridzuan, Perak, 2012)
The objective of this paper is to discuss the actual meaning and concept of Islamic Da’wah. The study implies that the whole Muslim ummah are responsible to convey the message of Islam, and it is not only the responsibility of individuals or certain groups of people. In order to ensure the effectiveness of da’wah, it must be done through a proper methodology and structured organization. It is suggested that more research should be conducted to ensure that the Muslim preachers can preach the message of Islam by using the contemporary method of da’wah or preaching.